Viability study of a high technology commercial aquaponics production system in São Paulo, Brazil - Araújo, Lorena Silva (2020)
The growing population needs to be fed. Nonetheless, with the current methods of harvesting fish and plants, we are depleting the world of its resources at a rate that cannot be replenished. As such, there is a need to develop a more sustainable farming method. Aquaponics is one of the possible solutions since it uses less water and space to produce both fish and plants with a recirculating nutrient-rich water where they can benefit from each other while using little to no fertilizer or pesticides. However, aquaponics is still not an established farming method due mainly to its complex knowledge base. Because of this, many systems fail and are not economically viable. In order for aquaponics to become more predominant, it needs to be able to compete economically with the traditional farming methods. This paper intends on showing if an aquaponics system can compete with traditional farming methods and under which conditions. The analysis was made as a case in São Paulo region competing with an ample traditional agriculture base. The results showed that a high-technology multi-loop system is viable and can compete as long as the right crop and scale is chosen. This comes to show that even in a region where there are many competitors (low price points), an aquaponics system can thrive and render economic results.